2012
DOI: 10.1017/s0033291712001225
|View full text |Cite
|
Sign up to set email alerts
|

Patients' beliefs about the causes, persistence and control of psychotic experiences predict take-up of effective cognitive behaviour therapy for psychosis

Abstract: BackgroundThere is evidence that patients with schizophrenia benefit from standard cognitive behaviour therapy (CBT) only if active techniques are used (‘full therapy’). By contrast, attending sessions but not proceeding beyond engagement and assessment strategies (‘partial therapy’), or simply not attending sessions (‘no therapy’), is not associated with better outcomes. The factors leading to full therapy are unknown. We hypothesized that patients' initial ideas about the nature and extent of their problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 33 publications
(47 reference statements)
3
64
1
4
Order By: Relevance
“…These items have been demonstrated to predict the uptake of psychological therapy [28]. Each item is rated from 1 (strongly disagree) to 5 (strongly agree), and psychometric properties are good.…”
Section: Methodsmentioning
confidence: 99%
“…These items have been demonstrated to predict the uptake of psychological therapy [28]. Each item is rated from 1 (strongly disagree) to 5 (strongly agree), and psychometric properties are good.…”
Section: Methodsmentioning
confidence: 99%
“…Effect sizes are in the small to medium range, and psychological interventions are only accessed by 15-30% of eligible service users [4][5][6][7][8]. Some people are not motivated to try therapy, and those that do may struggle to understand it and to apply new insights to everyday situations [9][10][11]. Efforts to improve effectiveness have focused so far on identifying causal mechanisms linked to specific outcomes and developing therapy techniques that target these mechanisms [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, medications alone are not sufficient for recovery in schizophrenia, and psychosocial treatments are a necessary complement (Kern et al, 2009). Three recent studies suggested that a psychosocial causal model could be relevant for treatment success by promoting non-pharmacological treatment (Sanders, et al, 2011; Lüllmann et al, 2011; Freeman et al, 2012). Causal beliefs may also act in divergent ways across the spectrum of treatment.…”
Section: Introductionmentioning
confidence: 99%